Law No. 69 of the year 2021 On Determining a Minimum Limit of the Periodic Raise Payable to the Workers Addressed by the Provisions of the Civil Service Law, Granting a Special Raise To the Workers Non-Addressed by the Provisions of the Civil Service Law and Increasing the Additional Incentive Payable to the State Civil Servants and Giving a Special Grant to the Workers of the Public Sector Companies and Public Business Sector Companies = قانون رقم 69 لسنة 2021 بتقرير حد أدنى للعلاوة الدورية للمخاطبين بقانون الخدمة المدنية ومنح علاوة خاصة لغير المخاطبين بقانون الخدمة المدنية وزيادة الحافز الإضافى للعاملين بالدولة وبتقرير منحة خاصة للعاملين بشركات القطاع العام وقطاع الأعمال العام - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic